The Antecedents of Consumer Satisfaction Toward OTT Platforms During COVID-19 Lockdown in India. (June 2023) - Verma, Saurabh; Yadav, Sunil Kumar
The outbreak of COVID-19 has emerged as the biggest threat to human life. It has changed the entire lifestyle of human beings concerning their emotional stability and cognitive development. Enjoyment is one of the emotions and acts as a positive stimulus that a consumer used to feel and seeks for a balanced life. Since the nationwide lockdown was implemented on March 25, 2020, people have turned restless about how to enjoy themselves at home, as all of their options of going out were being shattered. It was the time when continuous innovations in the form of digital content through over-the-top (OTT) platforms flourished and provided an affordable and diversified entertainment source to consumers. These OTT services help consumers to view the contents via the Internet directly. Furthermore, it has drastically changed people's preferences toward diversified content based on their choices. This study aims to explore the various determinants affecting consumer satisfaction toward the OTT platforms amid COVID-19 crisis in India. The study's main findings revealed that among the demographic variables, age group of the consumer largely influences their satisfaction toward OTT platforms. Moreover, work from home, affordability, convenience, and content quality are the significant determinants affecting consumer satisfaction levels toward OTT platforms. The study is relevant to the current marketing scenario, as it provides useful insights for the content developers of the major OTT platforms such as Amazon Prime, Netflix, Disney+ Hotstar, Voot, and many others to enhance the consumer satisfaction in the terms of digital content consumption.